EVALUASI SETAHUN PELAKSANAAN JAMINAN PERSALINAN DALAM MENURUNKAN ANGKA KEMATIAN IBU DAN BAYI - Claramita, Mora (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Proper insurance system is the first target of millennium development. Indonesian Ministry of Health offers an insurance system for helping reduce infant and maternal mortality rates: The Jampersal. Reproductive health for women and children is the second targets of MDGs . It has been 1 year of Jampersal implementation, therefore it needs to evaluate the effectiveness, especially in a remote area like Ternate in Northern Maluku. The study was conducted by collecting secondary quantitative data and primary qualitative data from 7 Puskesmas in Ternate (out of 8) in August-November 2012. Data were collected from 15 nursery mothers who underwent Jampersal insurance, from 15 midwives, 8 medical doctors and 1 obsgyn specialist from all districts Puskesmas in Ternate. Quantitative data were analyzed by descriptive statistics and qualitative data were analyzed by content analysis. that Jampersal was significantly increased documentation of medical record on mother who delivers the baby in Puskesmas; who were also increased in number. Previously lots of mother delivers at home with traditional birth attendances without proper documentation on medical records. It means that indirectly, Jampersal should have been helping in controling problems on reproductive and child health. However, it is not yet clear that Jampersal actually helps to reduce infant and maternal mortality rate due to many obstacles following the Jampersal implementations.